Prevention and management of common fracture complications - Archdeacon, Michael T. (SLACK, 2012)
"This is a quick reference guide for the prevention and treatment of common fracture complications, including the etiology of the complications, factors the surgeon can control in the operating room, and how to treat complications that arise"--